The Use of Classroom Repair in English Learning Classroom of UMS Students - Azkiya, Naurotu; Laila, Malikatul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The aim of this study is to identify the kinds of classroom repair in English learning classes of Universitas Muhammadiyah Surakarta (UMS) students. Methodology: This study uses a descriptive qualitative method. Data were collected from teacher and students’ utterances during classroom interactions. The techniques used include observation, voice recording, and note-taking. The analysis referred to Liddicoat’s (2007) theory of four types of repairs in conversation. Results: The results show that three types of classroom repair were found: (1) self-initiated self-repair, (2) other-initiated self-repair, and (3) other-initiated other-repair. The second type of Liddicoat’s model, self-initiated other-repair, was not observed in the data. Applications/Originality/Value: This research contributes to the educational field by providing insights into how repair strategies are used in English as a foreign language learning contexts. It emphasizes the importance of understanding conversational repair to enhance communication between teachers and students during the learning process.